Auditoría de gestión y su impacto en la rentabilidad de la Cooperativa de Ahorro y Crédito Occidental LTDA Cantón La Maná, periodo 2021 - Chango Llumitasig, Diego Wladimir (2022)
The present research entitled "MANAGEMENT AUDIT AND ITS IMPACT ON THE PROFITABILITY OF SAVINGS AND CREDIT COOPERATIVE OCCIDENTAL LTDA LA MANA CANTON, PERIOD 2021", whose main objective is to conduct a management audit and its impact on the profitability of Savings and Credit Cooperative Occidental LTDA, in La Maná Canton, period 2021. It was proposed due to the necessity of an evaluation of internal control to the agency, directed to the management of the resources that the purpose of the entity is to observe the impact presented within the profitability based on a non-experimental investigation with bibliographic foundation to have clear the basic concepts that were carried out in this applied investigation, in addition to being descriptive and field for the collection of the necessary information, the methods used in the research are deductive and analytical based on the techniques, such as surveys, questionnaires that were executed to the staff of the entity in the same way that the structured interview directed to the head of the agency was used, with the investigation it could be determined that its main strength is the loyalty of the partners and its problem is not having its own infrastructure, this was evidenced in the SWOT, which helped for the execution of the management audit that did not lead to three findings, which are lack of use of technology, the head of the agency does not make decisions and the processes are not respected, this affects the risk level is 21% which is low and the confidence level is 79% which is good for the cooperative, the identification of the need to have a manual of indicators within the agency is essential to better distribute the resources.